Prolactin synergizes with canonical Wnt signals to drive development of ER+ mammary tumors via activation of the Notch pathway. (10th April 2021) - O'Leary, Kathleen A.; Rugowski, Debra E.; Shea, Michael P.; Sullivan, Ruth; Moser, Amy R.; Schuler, Linda A.
Abstract: Prolactin (PRL) cooperates with other factors to orchestrate mammary development and lactation, and is epidemiologically linked to higher risk for breast cancer. However, how PRL collaborates with oncogenes to foster tumorigenesis and influence breast cancer phenotype is not well understood. To understand its interactions with canonical Wnt signals, which elevate mammary stem cell activity, we crossed heterozygous NRL-PRL mice with Apc Min/+ mice and treated pubertal females with a single dose of mutagen. PRL in the context of Apc Min/+ fueled a dramatic increase in tumor incidence in nulliparous mice, compared to Apc Min/+ alone. Although carcinomas in both NRL-PRL/ Apc Min/+ and Apc Min/+ females acquired a mutation in the remaining wildtype Apc allele and expressed abundant β-catenin, PRL-promoted tumors displayed higher levels of Notch-driven target genes and Notch-dependent cancer stem cell activity, compared to β-catenin-driven activity in Apc Min/+ tumors. This PRL-induced shift to dominant Notch signals was evident in preneoplastic epithelial hyperplasias at 120 days of age. In NRL-PRL/ Apc Min/+ females, rapidly proliferating hyperplasias, characterized by β-catenin at cell junctions and high NOTCH1 expression, contrasted with slower growing lesions with nuclear β-catenin in Apc Min/+ females. These studies demonstrate that PRL can powerfully modulate the incidence and phenotype of mammary tumors, shedding light on mechanisms whereby PRL elevates risk of breast cancer. Highlights: Prolactin dramatically increased mammary tumor incidence in the context of Apc Min/+ . Prolactin/ Apc Min/+ tumors exhibited Notch-rather than Wnt-dependent CSC activity. Prolactin induced Notch dominance and rapid proliferation in early lesions.